Risks and Crises for Healthcare Providers: The Impact of Cloud Computing - Ronald Glasberg; Michael Hartmann; Michael Draheim; Gerrit Tamm; Franz Hessel (The Scientific World Journal)
We analyze risks and crises for healthcare providers and discuss the impact of cloud computing in such scenarios. The analysis is conducted in a holistic way, taking into account organizational and human aspects, clinical, IT-related, and utilities-related risks as well as incorporating the view of the overall risk management.